CAI 변별 자질 프로그램이 청각장애아동의 어음변별력에 미치는 효과 - 권순우(Soon-Woo Kwon); 남윤석(Yun-Sug Nam) (언어치료연구, 2008)
본 연구의 목적은 청각장애아동의 어음변별력을 증진시키기 위해 개발된 CAI 변별 자질 프로그램의 적용 효과를 알아보기 위한 것이다. 이를 위하여 청각장애 특수학교 초등부 1, 2학년에 재학 중인 수반장애가 없는 순수 청각장애아동 9명을 대상으로 일주일에 2회씩 총 16회기 동안 CAI 변별 자질 프로그램을 활용한 교수 · 학습 계획을 구안하여 교실 수업에 적용하였다. 연구 결과는 CAI 변별 자질 프로그램이 청각장애아동의 어음변별 과제(그림자 맞추기 · 글자 맞추기 · 상황에 맞는 그림 찾기) 수행 능력의 향상에 효과적인 것으로 나타났다. The purposes of the study were to verify effectiveness of the CAI program for teaching speech discrimination to children with hearing impairment. The total sample is 9 subjects with only hearing impairment in first and second grades of special education school. This study uses one group pre-/post-test design. This study is performed total of 16 times, 2 times a week with CAI program in classroom. The results of this study are as follows: The instruction used CAI program was effective on the progress of speech discrimination(matching shadow tasks, matching letter tasks, and finding suited picture in situation tasks) among the children with hearing impairment. KCI Citation Count: 2